(3Qei GdfTGHs - (3eMeO Hf Ydj GdUZjQ, eYde GdfTGHs
(3ChdgG (B:s
(3hHYO , aeG cGfJ gPg GdUfGYI ef Cge GdCehQ hCTQagG hCYRgG hCcQegG s
(3BNQgG (B:s
(3hCSCd Gddg SHMGfg hJYGdi Cf jLYd gPG GdeNJUQ fGaYkG s
(3fSNJjf efgs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B136 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeI (B- (3U (B16 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs